2007
DOI: 10.1007/s11010-006-9401-6
|View full text |Cite
|
Sign up to set email alerts
|

High glucose promotes the production of collagen types I and III by cardiac fibroblasts through a pathway dependent on extracellular-signal-regulated kinase 1/2

Abstract: Hyperglycemia promotes fibrosis by increasing collagen synthesis, a process involving mitogen activated protein kinases (MAPKs). Several studies of diabetic cardiomyopathy have demonstrated an accumulation of collagen, including collagen types I and III, in the myocardium, leading to interstitial fibrosis, which is related to left-ventricular diastolic dysfunction. However, the mechanisms of hyperglycemia-induced collagen production in cardiac fibroblasts are poorly defined. In the present study, neonatal rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 25 publications
6
49
1
1
Order By: Relevance
“…mesangial cells, and vascular smooth muscle cells contribute to the cardiovascular and nephritic complications of diabetes (Neumann et al 2002, Tokudome et al 2004, Maile et al 2010, and ERK1/2 activation has been linked to high glucose-induced fibrosis (Tang et al 2007). Consistent with these previous reports, high glucose presently increased cell proliferation and affected the expression of ECM-related genes in cardiac fibroblasts by modulating ERK activities.…”
Section: Discussionsupporting
confidence: 78%
“…mesangial cells, and vascular smooth muscle cells contribute to the cardiovascular and nephritic complications of diabetes (Neumann et al 2002, Tokudome et al 2004, Maile et al 2010, and ERK1/2 activation has been linked to high glucose-induced fibrosis (Tang et al 2007). Consistent with these previous reports, high glucose presently increased cell proliferation and affected the expression of ECM-related genes in cardiac fibroblasts by modulating ERK activities.…”
Section: Discussionsupporting
confidence: 78%
“…Glucose (25 mmol/L) has also been shown to stimulate the phosphorylation of ERK1/2 in cardiac fibroblasts [12] . There were rare reports about the effect of glucose on the phosphorylation of NF-κB in cardiac fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Modulation of fibrosis signals in response to glucose and angiotensin II Previous studies have demonstrated that high concentrations of glucose promote cardiac secretion of collagens by fibroblasts [12] . In this study, we found that the expression of fibronectin, collagen-3A and collagen-4A was markedly increased in cardiac fibroblasts in response to glucose or Ang II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac fibroblasts also take a part in the maintenance of myocardial function by producing the type I and type III collagens and by secreting growth factors (48), and a key source of components of the ECM that regulates the structure of the heart and hence mechanical, chemical, and electrical signals between cellular and noncellular components (54). Thus cardiac fibroblasts play an essential role in the fibrosis and remodeling by increased proliferation (4) and elevated collagen production (61) under the various pathophysiological conditions such as diabetic cardiomyopathy (41).…”
mentioning
confidence: 99%